Sharia Crowdfunding as a Source of Funding for Halal Creative Industries in Indonesia - Ariyanti, Yulia Dewi; Dwi Novaria Misidawati; Syifa Rohmah (Sahmiyya: Jurnal Ekonomi dan Bisnis, 2025)
The halal creative industry is growing in Indonesia, driven by the increasing demand for sharia-based products and services. One of the main challenges of this industry is the limited access to funding sources that comply with sharia principles. Islamic crowdfunding comes as an alternative solution that allows the community to contribute to the funding of halal creative industry projects collectively. This research uses the literature review method to analyze the concept, implementation, and challenges of sharia crowdfunding as a source of funding for the halal creative industry. Data is obtained from relevant journals, articles, books, and research reports. The analysis was carried out with a qualitative descriptive approach to understand the sharia crowdfunding mechanism and its impact on the halal creative industry. The results showed that Islamic crowdfunding has great potential in supporting the halal creative industry by providing access to financing based on the principles of justice, transparency, and profit sharing (mudharabah and musyarakah). However, the main challenges in its implementation include low Islamic financial literacy among the public, regulations that are still developing, and the risk of fraud and default. Supervision from sharia authorities as well as the development of stricter regulations are needed to increase the trust and effectiveness of this system. Islamic crowdfunding is an innovative solution for funding halal creative industries that can increase the inclusiveness of the Islamic economy. It is recommended that there should be wider Islamic financial education and more comprehensive regulatory support so that this financing model can develop optimally and sustainably.